Kualitas Pelayanan Dan Pengaruhnya Terhadap Kepuasan Pelanggan (Studi Pada Pemerintah Kabupaten Barito Selatan Kalimantan Tengah) - Rahmi Widyanti; - Kurniaty (Conference In Business, Accounting, And Management (CBAM), 2012)
This study aims to test the relationship between service quality to increase customer’s satisfaction of East Barito Local Goverment Central Kalimantan. Data were collected from societies of East Barito Local Goverment Central Kalimantan, 269 questionnaires were collected with cluster sampling and analyzed using statistical techniques Statistical Product and Service Solutioan (SPSS). The open questions are presented to explain service quality which a people needed. This study found that was strong influence of service quality to increase customer’s satisfaction are positively and significant affects directly. Build from the value of relationships of variables of service quality and customer satisfaction, it is obtain that the indicator of empathy is the most powerful indicator. Findings thisresearch proved that service quality to increase customers satisfaction. Even though value of this research could additional new framework of the human resource and marketing literature on two variables: service quality and customers satisfaction specially servive on government citizen of East Barito Local Goverment Central Kalimantan, which could be used in increasing customers satisfaction. However there are limitations in used statistical techniques and has not tested these variables results from service quality to increase customer’s satisfaction.Keyword : service quality, customers satisfaction